2022
DOI: 10.18016/ksutarimdoga.vi.896094
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Contract Farming on Beef Cattle Farmers' Income: A Propensity Score Matching Analysis

Abstract: This study aims to investigate the impact of contract farming participation on the income of beef cattle farmers. For this purpose, the data was collected from 155 farmers by face-to-face questionnaires in Adana province in 2016. The impact of contract farming on farmers’ income was identified using Propensity Score Matching. The results show that farmers who participate in the contract have more assets and mostly have a larger herd in comparison with non-contract. Further, contract participation entails a 10.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…This insurance of soybean is to contribute to food security and nutritional by generating additional incomes to small producers (Ministry of Agriculture, Foreign and Fisheries, 2019). Several studies focused on the impact of the Farming Contract on Food Security (Ndlovu et al, 2022); income (Ağir & Akbay, 2022a); The technical effectiveness of producers (Hariento et al, 2019a, Paltashingh & Jena, 2023A, Selim et al, 2023) and on the economic efficiency of farms ... Most studies have therefore been interested in the impact of the Farming Contract on several indicators as cited above.…”
Section: Introductionmentioning
confidence: 99%
“…This insurance of soybean is to contribute to food security and nutritional by generating additional incomes to small producers (Ministry of Agriculture, Foreign and Fisheries, 2019). Several studies focused on the impact of the Farming Contract on Food Security (Ndlovu et al, 2022); income (Ağir & Akbay, 2022a); The technical effectiveness of producers (Hariento et al, 2019a, Paltashingh & Jena, 2023A, Selim et al, 2023) and on the economic efficiency of farms ... Most studies have therefore been interested in the impact of the Farming Contract on several indicators as cited above.…”
Section: Introductionmentioning
confidence: 99%
“…Studies indicate that the health expenditures reported in our country since year 2000 have increased in the following years, likely due to the increase in public health expenditures and most of these expenditures relate to hospital and pharmaceutical expenditures. 1…”
Section: Introductionmentioning
confidence: 99%